Reading Books Live On Tiktok: Is It Legal. - Justine, Gabriele (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
This study examines the copyright law of Indonesia and the legality of reading aloud a book on a live TikTok. The purpose is to comprehend the legal implications and ethical considerations of doing so based on Indonesian copyright law. The study employs a normative legal research method, where applicable legal norms and legal doctrines pertaining to copyright infringement in the context of live reading of books on TikTok. The study employs a statute approach, juxtaposing relevant laws that govern copyright and the exploitation of copyrighted works in the TikTok platform. A conceptual approach is used to analyze legal concepts relating to copyright and the exploitation of works on social media. Qualitative analysis is conducted to identify and analyze relevant legal issues surrounding copyright infringement in live book reading on TikTok. Document analysis and study conclusions contribute to a general understanding of copyright infringement challenges in a context of TikTok. The objective of the present study is to provide a general legal analysis of the practice of reading aloud a book during a live TikTok session based on copyright infringement.